1987
DOI: 10.1007/bf02491490
|View full text |Cite
|
Sign up to set email alerts
|

A complete class for linear estimation in a general linear model

Abstract: SummaryIt is shown that in linear estimation, both unbiased and biased, all unique (up to equivalence with respect to risk) locally best estimators and their limits constitute a complete class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Note that using Theorem 2.2 we get all admissible linear estimators of K EY among L. This is due to the fact that every ULBE is admissible among L (see LaMotte [12]) and that all ULBE's and their limits constitute a complete class (see Stȩpniak [21] and LaMotte [13]). …”
Section: Models With Finitely Generated Parameter Spacementioning
confidence: 97%
See 1 more Smart Citation
“…Note that using Theorem 2.2 we get all admissible linear estimators of K EY among L. This is due to the fact that every ULBE is admissible among L (see LaMotte [12]) and that all ULBE's and their limits constitute a complete class (see Stȩpniak [21] and LaMotte [13]). …”
Section: Models With Finitely Generated Parameter Spacementioning
confidence: 97%
“…The first set contains the second one. Using Bayes DOI: 10.14736/kyb-2016-5-0724 approach this was proved by Stȩpniak [21] but his proof was not constructive. LaMotte [13] presented a construction of a sequence of unique locally best linear estimators that converged to the given admissible linear estimator.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of characterizing admissible linear estimators of a linear function of expected value was also considered in terms of connection between the closure of the set of unique locally best estimators (ULBE) and the set of admissible linear estimators. This approach was applied, among others, by Stępniak [23], Zontek [29] and LaMotte [15]. LaMotte has shown that every admisible linear estimator is the limit of linear estimators that are uniquely best at points in the minimal closed convex cone containing the original parameter set.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent works by Stępniak [23], Zontek [29], LaMotte [15] and Synówka-Bejenka and Zontek [28] introduced a new tool in the problem of admissibility. It is based on the DOI: 10.14736/kyb-2014- limits of the unique locally best linear estimators.…”
Section: Introductionmentioning
confidence: 99%